The Implementation Of Teacher Performance Assessment Through Promethee Method Approach (Case Study At Smkn 5 Seluma) - Guritno Adianto; Dewi Suranti; Aji Sudarsono (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
SMK Negeri 5 Seluma is one of the Vocational Schools in Seluma Regency, Bengkulu Province. At the school in every year a Teacher Performance Assessment or what is often referred to as PKG is carried out. There are 14 assessment criteria for teacher performance which are divided into 4 categories of assessment, namely Pedagogic, Personality, Social and Professional. So far, the processing of teacher performance assessment data has used the office application package, namely Excel (data attached) to provide grades and calculate the PKG scores obtained by the teacher in accordance with the applicable provisions. The implementation for assessing teacher performance at SMK Negeri 5 Seluma using Promethee Method was created using the Visual Basic.Net programming language (IDE Visual Studio 2010) and SQL Server 2008 database. The application for assessing teacher performance at SMK Negeri 5 Seluma it can be used as an alternative in helping to assess assessment of teachers in schools, so that it can be seen who has the best performance based on the ranking results obtained from the promethee. The application for assessing teacher performance at SMK Negeri 5 Seluma has applied Promethee method, so that the final assessment results for each teacher have gone through the calculation procedure for the Promethee method. The final assessment results will be sorted from the highest value to the lowest value by looking at the net flow value which is the result of subtracting the leaving flow and entering flow. Based on testing using 5 (five) teacher performance assessment data in 2019, the results obtained that Guru Isuadi, S.Pd got the highest score with a leaving flow value of 1.63, entering flow 1.63 and net flow 1.63. Based on the results of the same assessment on manual calculations, it is found that the results of calculations on the decision support system had the same value as the results of manual calculations that had been carried out. Applications can be used as an alternative in providing an assessment of teacher performance in schools.